Awareness and Readiness to Integrate AI with Traditional Library Services in Kwara State - Suebat Ajoke Busari; Amina Alhassan Idris (Mimbar Ilmu, 2025)
The rapid integration of computer-based technologies has transformed the ways knowledge is created, accessed, and disseminated, while also presenting both opportunities and challenges for academic libraries. Traditional library services, although long established and essential, are under pressure to adapt to emerging technologies such as artificial intelligence (AI). This study aims to critically analyze the awareness and readiness of academic library users to integrate AI into conventional library services, balancing innovation with tradition. A descriptive survey design was employed, involving 150 respondents, of which 120 valid responses were further analyzed. Data were collected using a structured questionnaire and analyzed through descriptive statistics, including frequencies and percentages. The findings reveal that respondents’ level of awareness falls within the moderate category, with varying degrees of readiness to embrace AI implementation for enhancing library functions. The study concludes that although AI holds transformative potential for academic libraries, its successful adoption requires continuous user education, librarian capacity building, and supportive institutional policies. The implications highlight the importance of strategically integrating AI to ensure that libraries remain relevant, accessible, and innovative while preserving the strengths of traditional services.